RESPON EMOSI YANG MUNCUL SAAT MENGALAMI TAKHAYUL - Salamah, Yusril Umi; Muhammad, Amri Hana (Fakultas Psikologi Universitas Hang Tuah, 2023)
Abstract. Individuals experiencing superstitions respond with varied emotions. Do individuals experiencing negative superstitions respond with negative emotions, while individuals experiencing positive superstitions will respond with positive emotions? How is emotional arousal depicted when people experiencing superstitions? This study aimed to determine the emotional responses associated with negative and positive superstitions and the description of emotional arousal. The research design used was descriptive quantitative research. The population for this study consisted of Javanese individuals with a sample size of 192 subjects. The research respondents were selected using incidental sampling techniques and were given questionnaires to collect the data. The instruments used in this study were treatment and data collection instruments. The results of descriptive analysis revealed that individuals experiencing negative superstitions had emotions of fear, calm, non-specific emotions and guilt. Furthermore, individual experiencing positive superstitions had the emotions of calmness, hope, gratitude and joy. The level of emotional arousal when experiencing negative superstitions was categorized as medium, whereas the level of emotional arousal when experiencing positive superstitions was categorized as high.